EVALUATING COMPANY PERFORMANCE THROUGH THE USE OF BENCHMARKING - Kožená, Marcela; Kočvarová, Lucie (STEF92 Technology Ltd., 2017)
The concept of benchmarking can be defined in many ways. In general it is a method of increasing the performance and competitiveness of a company on the basis of comparing oneself with the best in a given field. The objective of this method is to gain information that will help to identify the strengths and weaknesses of a company with its competitors and which will serve as inspiration for improvement. Information is gained by constant observation and evaluation. At present, businesses, if they want to be competitive, should use this management tool to continually improve their performance across all company processes and activities. The professional literature presents different types of benchmarking; based on the organisation or field being compared, we can distinguish between performance, functional and process benchmarking. In practice, benchmarking uses a number of models; among the most well-known are the Xerox Corp., the American Productivity and Quality Center (APQC), the European Foundation for Quality Management (EFQM) or the Ontario Municipal Benchmarking Initiative (OMBI). Based on surveys conducted by Bain & Company on a long-term basis, benchmarking is one of the most popular and commonly used management tools, followed by strategic planning, customer relationship management, outsourcing, and vision and mission statements. The subject matter of this paper is the implementation of performance benchmarking in two Czech companies dealing with agricultural production. The aim of the benchmarking comparison is to identify the differences in the development of their financial situation, as well as to evaluate the specific indicators characteristic of agricultural production. In addition to the proportional indicators of the financial analysis, this paper includes a comparison of the subsidies drawn upon, the size of the land and selected cost items.
HODNOCENÍ VÝKONNOSTI PODNIKU S VYUŽITÍM METODY BENCHMARKINGU
Keywords: Benchmarking; performance; company; financial analysis; customer; Benchmarking; výkonnost; podnik; finanční analýza; zákazník